2022
DOI: 10.1155/2022/2044577
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid as a Potential Inhibitor against the Nonstructural Protein NS3 Helicase of Zika Virus: A Molecular Modelling Study

Abstract: Zika virus is a member of the Flaviviridae family and genus Flavivirus, which has a phylogenetic relationship with spondweni virus. It spreads to humans through a mosquito bite. To identify potential inhibitors for the Zika virus with biosafety, we selected natural antiviral compounds isolated from plant sources and screened against NS3 helicase of the Zika virus. The enzymatic activity of the NS3 helicase is associated with the C-terminal region and is concerned with RNA synthesis and genome replication. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The ellagic acid inhibited human rhinoviruses HRV-2, -3, and -4, with higher activity than ribavirin used as a control antiviral drug [ 29 ]. Recently, ellagic acid was identified as a potential inhibitor of NS3 helicase of the Zika virus, an arbovirus belonging to the Flaviviridae family [ 30 , 31 ]. Cui et al [ 32 ] reported that ellagic acid and gallic acid exert antiviral activity against the Ebola virus by inhibiting virus entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The ellagic acid inhibited human rhinoviruses HRV-2, -3, and -4, with higher activity than ribavirin used as a control antiviral drug [ 29 ]. Recently, ellagic acid was identified as a potential inhibitor of NS3 helicase of the Zika virus, an arbovirus belonging to the Flaviviridae family [ 30 , 31 ]. Cui et al [ 32 ] reported that ellagic acid and gallic acid exert antiviral activity against the Ebola virus by inhibiting virus entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, presents four rings representing the lipophilic domain, four phenolic groups, and two lactones, which form hydrogen-bonds sides and act as electron acceptors respectively, and that represents the hydrophilic domain [32]. In addition, ellagic acid has been reported to possess antiviral activity demonstrated by in vitro models [33]. Moreover, in an in vitro study, it was reported that of the identified specialized metabolites in Punica granatum (Pomegranate), ellagic acid was one of the compounds that exhibited the most relevant inhibition of HIV-1 RT-associated ribonuclease H (RNase H) and HIV-1 integrase (IN) lens epithelium-derived growth factor (LEDGF)-dependent activities [34].…”
mentioning
confidence: 99%